Differences in physical activity levels in 8-10 year-old girls who attend physical education classes only and those who also regularly perform extracurricular sports activities - ÇAMLIGÜNEY, ASİYE FİLİZ (ELSEVIER SCIENCE BV, 2012)
The aim of this study is to determine the differences in physical activity levels (PAL) of 8-10 year-old girls, who attend physical education (PE) classes only and those who also regularly perform extracurricular sports activities, and to study the relationship between PAL and body composition. 35 primary school girls of 8-10 years of age have participated this study. Control group (n=17) consisted of girls who attended physical education classes 2 hours per week, experimental group (n=18) consisted of girls who, in addition to physical education classes, participated in volleyball training. Extracurricular Sports activities must be supplement PE classes.
Keywords: Physical Education; Physical Activity; Pedometry; Girl; CHILDREN; RECOMMENDATIONS; GUIDELINES; YOUTH